Internetworking over ATM - Brian Dorling (Prentice Hall PTR, 1996)
Introduction; Emulated and virtual Lans; Multiprotocol over ATM (MPOA); APPN Support in ATM networks; IP support in ATM networks; PNNI phase 1 and integrated PNNI; Switched virtual networking architecture; The future of IP; Protocol stack reference.